Between Harmony and Discrimination. - Nothaft, C. Philipp E. (Brill's Southeast Asian library., 2014)
Between Harmony and Discrimination articulates how religious practices have become the primary identity markers in Bali and Lombok. This movement has caused the historic interreligious relationships between majority and minority populations, primarily Hindus and Muslims, to be renegotiated and reconfigured.